Scrutinizing Register Realization in Facebook Trading Group - Antonius Setyawan Sugeng Nur Agung; Monika Widyastuti Surtikanti; Masfa Maiza; Efrika Siboro (Register Journal, 2022)
This study aims at scrutinizing the register pattern used by the sellers in promoting their goods in the popular Facebook trading group used by people in Ngabang, West Borneo, “Ngabang Jual-Beli”. The group is an ambient representation of language variation used in West Borneo. The register analysis covers the field, tenor, and mode of the discourse. The data analysis encompasses domain, taxonomy, componential, and cultural theme analysis modified by Santosa (2017). The domain covers the kinds of goods being sold. The taxonomy analysis is the three meta functions in the SFL framework. The combined domain and taxonomy in the componential analysis figure out the register pattern in the group. The findings reveal that in the field of discourse, the posted clauses are dominated by the use of the material process, relational identification, and relational attributive process. The material process reflects the experiential meaning of the current activities. Meanwhile, the information of the goods realizes relational identification and relational attributive processes. With respect to the tenor of discourse, there is a tendency for the sellers to use declarative clauses which reflect equal status between the sellers and the customers by considering the minimal social distance. Furthermore, in the mode of discourse, the unmarked topical theme reflects as the majority of the ellipsis subject referring to the sellers. The study implies that the language used in digital trading should consider the participants, the relationship among the participants, and the media used to persuade their target market.Keywords: Facebook trading group, online shop, register, systemic functional linguistics